Strategi Komunikasi Pariwisata dalam Meningkatkan Jumlah Kunjungan Pada Tradisi Pacu Jalur Sebagai Atraksi Wisata Budaya - Habibisalam .; Ria Edlina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Pacu Jalur has developed into one of the cultural tourism attractions that attracts the attention of both domestic and international tourists. In this context, promotion becomes an important element to attract more visitors and promote local cultural values. The Kuantan Singingi Regency Government has a vital role in managing and promoting Pacu Jalur to remain relevant and attractive to the tourism market. The theory used in this study is the Marketing Communication Mix Theory. The method used in this study is a qualitative descriptive approach, this approach is used because the data used in compiling this thesis are in the form of descriptions, explanations, and information regarding problems that occur in the field or research location. The techniques used in this study are interview techniques, observation techniques, and documentation techniques. Data analysis techniques used in qualitative research include data reduction, data presentation and conclusion drawing. The data in this study were tested using data source triangulation. Based on the data obtained from the results of the study of Tourism Communication Strategy in Increasing the Number of Visits to the Pacu Jalur Tradition as a cultural tourism attraction that the Department of Tourism and Culture uses social media as a form to introduce and increase visits from Pacu Jalur tourists as a Cultural Attraction. In addition to utilizing social media, the Department of Tourism and Culture also employed strategic outreach and involved community leaders and the surrounding community in the preparation and implementation of the Pacu Jalur program. The Department of Culture faced several significant obstacles. One of the main obstacles was limited infrastructure and access to information in several areas, particularly in rural areas where internet and digital media networks were not yet fully accessible. This resulted in uneven distribution of promotional information and a suboptimal reach for all levels of society. Furthermore, other challenges faced were limited promotional budgets and human resources with a professional understanding of digital-based communication strategies.